The ethics of human volunteer studies involving experimental exposure to pesticides: unanswered dilemmas - London Leslie; Coggon David; Moretto Angelo; Westerholm Peter; Wilks Martin F; Colosio Claudio (BMC, 2010)
Abstract The controversy about the use of data from human volunteer studies involving experimental exposure to pesticides as part of regulatory risk assessment has been widely discussed, but the complex and interrelated scientific and ethical issues remain largely unresolved. This discussion paper, generated by authors who comprised a workgroup of the ICOH Scientific Committee on Rural Health, reviews the use of human experimental studies in regulatory risk assessment for pesticides with a view to advancing the debate as to when, if ever, such studies might be ethically justifiable. The discussion is based on three elements: (a) a review of discussion papers on the topic of human testing of pesticides and the positions adopted by regulatory agencies in developed countries; (b) an analysis of published and unpublished studies involving human testing with pesticides, both in the peer-reviewed literature and in the JMPR database; and (c) application of an ethical analysis to the problem. The paper identifies areas of agreement which include general principles that may provide a starting point on which to base criteria for judgements as to the ethical acceptability of such studies. However, the paper also highlights ongoing unresolved differences of opinion inherent in ethical analysis of contentious issues, which we propose should form a starting point for further debate and the development of guidelines to achieve better resolution of this matter.